Pengaruh Green Perceived Value, Environmental Knowledge, Green Brand Image Terhadap Green Purchase Intention pada Produk Sensatia Botanicals - Rismayanti, Rismayanti; Harsoyo, Titik Desi (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the influence of Green Perceived Value, Environmental Knowledge, Green Brand Image on Green Purchase Intention on Sensatia Botanicals products. The sample in this study was 100 respondents who had never purchased Sensatia Botanicals products and knew that Sensatia Botanicals products were environmentally friendly products. The results of the instrument test stated that all question items used in this instrument were valid and reliable. The results of the classical assumption test stated that the data in this study were normally distributed and free from multicollinearity and heteroscedasticity. Based on the results of the study, it can be proven that (1) Green Perceived Value has a negative and significant effect on Green Purchase Intention on Sensatia Botanicals products. (2) Environmental Knowledge has a positive and significant effect on Green Purchase Intention on Sensatia Botanicals products. (3) Green Brand Image has a positive and significant effect on Green Purchase Intention on Sensatia Botanicals products.